2013
DOI: 10.5194/se-4-167-2013
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of land use change in soil carbon and nitrogen in a Mediterranean agricultural area (Southern Spain)

Abstract: Abstract. The agricultural Mediterranean areas are dedicated to arable crops (AC), but in the last decades, a significant number of AC has led to a land use change (LUC) to olive grove (OG) and vineyards (V). A field study was conducted to determine the long-term effects (46 years) of LUC (AC by OG and V) and to determine soil organic carbon (SOC), total nitrogen (TN), C : N ratio and their stratification across the soil entire profile, in Montilla-Moriles denomination of origin (D.O.), in Calcic-Chromic Luvis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 68 publications
(68 reference statements)
3
71
1
Order By: Relevance
“…It has been shown that N mineralization decreases when clay content increases in soil (Côté et al, 2000;Corral-Fernández et al, 2013;Parras-Alcántara et al, 2013). In the 0-80 cm soil profiles, the average silt and sand contents were 56.0% and 41.1%, respectively.…”
Section: Figmentioning
confidence: 89%
“…It has been shown that N mineralization decreases when clay content increases in soil (Côté et al, 2000;Corral-Fernández et al, 2013;Parras-Alcántara et al, 2013). In the 0-80 cm soil profiles, the average silt and sand contents were 56.0% and 41.1%, respectively.…”
Section: Figmentioning
confidence: 89%
“…Gallardo et al (2000) showed that the low OM content could be explained by the semiarid Mediterranean conditions. In addition, Parras-Alcántara et al (2013a) found there is less OM and fewer mineral aggregates in sandy soils, thus favoring high levels of OM transformation. Because of this, Hontoria et al (2004) suggested that physical variables determine soil development in the driest areas of Spain to a greater degree than management or climatic variables.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…Munoz-18 Rojas et al 2012;De Moraes Sá et al 2013;Gelaw et al 2013;Parras-Alcántara et al 2013, 201419 Srinivasarao et al 2014;Yu and Jia 2014;Behera et al 2015;Peng 2015). Agriculture can strongly 20 limit SOM accumulation, influencing soil aggregate formation and turnover (Jastrow 1996;Cerdà, 21 2000;Jacobs et al 2010;Gosling et al 2013).…”
Section: Introductionmentioning
confidence: 99%